Can we predict the magnetic properties of PMS stars from their H-R diagram location?. Issue Volume 9:Issue S302(2013) (7th August 2014) - Gregory, S. G.; Donati, J.-F.; Morin, J.; Hussain, G. A. J.; Mayne, N. J.; Hillenbrand, L. A.; Jardine, M.
Abstract: Spectropolarimetric observations combined with tomographic imaging techniques have revealed that all pre-main sequence (PMS) stars host multipolar magnetic fields, ranging from strong and globally axisymmetric with ≳kilo-Gauss dipole components, to complex and non-axisymmetric with weak dipole components (≲0.1 kG). Many host dominantly octupolar large-scale fields. We argue that the large-scale magnetic properties of a PMS star are related to its location in the Hertzsprung-Russell diagram. This conference paper is a synopsis of Gregory et al . (2012), updated to include the latest results from magnetic mapping studies of PMS stars.